The Role of Local Wisdom-Based Disaster Education and Training Through Education Levels in Disaster-Prone Areas - Zainul Hidayat; Mimin Yatminiwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to find out conceptually-theoretically disaster education and training based on local wisdom can strengthen the character of disaster preparedness. The method used in this study is the library research method, or it can also be called the literature review method, which is a type of study conducted by reviewing relevant relevant literatures. Based on the results of data analysis, it can be concluded that the application of disaster education and training based on local wisdom can improve the character of student preparedness. So that the stronger the character of student preparedness can reduce the risk in the event of a disaster. One of the reasons for the high number of casualties and property losses due to disasters is the lack of preparedness for a disaster. The character of disaster preparedness is certainly not formed instantly, but goes through a long process. Disaster education and training based on local wisdom is the right step in strengthening the character of disaster preparedness in students. Disaster education is very important to be held starting from basic education to higher education.